2012
DOI: 10.1371/journal.pone.0031409
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Malaria in Zambezia, Mozambique: The Protective Effect of IRS versus Increased Risks Due to Pig-Keeping and House Construction

Abstract: BackgroundAfrican countries are scaling up malaria interventions, especially insecticide treated nets (ITN) and indoor residual spraying (IRS), for which ambitious coverage targets have been set. In spite of these efforts infection prevalence remains high in many parts of the continent. This study investigated risk factors for malaria infection in children using three malaria indicator surveys from Zambezia province, Mozambique. The impact of IRS and ITNs, the effects of keeping farm animals and of the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 31 publications
10
69
5
Order By: Relevance
“…This study did not find any association between education of parents/guardians and malaria infection in children. This is however, contrary to results of other studies [12], where Children of educated parents …”
Section: Socio-economic and Demographic Risk Factorscontrasting
confidence: 99%
See 1 more Smart Citation
“…This study did not find any association between education of parents/guardians and malaria infection in children. This is however, contrary to results of other studies [12], where Children of educated parents …”
Section: Socio-economic and Demographic Risk Factorscontrasting
confidence: 99%
“…Other studies have reported that educational level of an individual particularly that of a child's caregiver, has been shown to be an important risk factor of malaria [12,13]. It is assumed that more educated individuals have a better understanding of health-related issues.…”
Section: Journal Of Transmitted Diseases and Immunity Issn 2573-0320mentioning
confidence: 99%
“…When looking at these variables individually without adjusting for SES, grass roofing was associated with P. falciparum infection after adjusting for age and background malaria transmission; wall and floor material were not associated. Temu and collegues also found an association between grass roofing and malaria infection [58]. However, in this study it cannot be determined whether grass roofing was a risk factor in itself by providing shelter for mosquitoes, or whether it was just a good proxy for SES.…”
Section: Discussionmentioning
confidence: 61%
“…[4][5][6][7] Poor-quality household construction materials have also been associated with increased mosquito entry, malaria incidence, and parasite prevalence. 4,5,[8][9][10][11] Several studies classify housing structures into quality groupings according to the composition of the construction materials have found poor house quality to be associated with greater presence of mosquitoes in the home and higher malaria incidence. 12,13 We recently completed a randomized control trial of malaria chemoprevention in a cohort of 600 children from different households followed from 6 months to 2 years of age in a rural area of Uganda where malaria is highly endemic.…”
Section: Introductionmentioning
confidence: 99%